Evaluation of the Diagnostic Value of Calretinin Immunohistochemistry Assay in the Superficial Rectal Biopsy of Children Suspected of Hirschsprung's Disease - Azar Naimi; Elahe Shegeft (Mashhad University of Medical Sciences, 2022)
Background: Hirschsprung's disease (HD) is the most common cause of colon obstruction in neonates. Lack of calretinin immunohistochemistry (IHC) in colon lamina propria could be associated with aganglionosis. Methods: This cross-sectional retrospective study examined 64 patients suspicious of HD and conducted on collected-demographic data and Hematoxylin/Eosin (H & E) results of the surgical rectal biopsy from the archive of Imam Hossein Hospital, Isfahan, Iran. Calretinin IHC was achieved for all the specimens, and the results of the two methods were compared. The receiver operating characteristic (ROC) chart shows sensitivity changes according to (1-specificity). Moreover, sensitivity, specificity, as well as the positive and negative predictive values (PPV and NPV) of calretinin staining in lamina propria and muscularis mucosa, compared to H & E staining, was calculated in this study. Results: The number of males and females was the same in this study (n=32; 50%). The age of the patients ranged from 1 month to 156 months (13 years). Out of 64 patients, 8 cases were diagnosed with HD, and calretinin staining was negative in 7 patients; moreover, only one case showed weak positive staining. In 56 patients, who were not HD, two patients with negative calretinin staining had a positive H&E staining report. The current study aimed to check the diagnostic value of calretinin IHC in lamina propria of patients suspicious of HD. Compared to H&E staining, which is the routine method in thick wall biopsies, the statistics show that calretinin IHC has a high diagnostic value (P<0.001), sensitivity of 87%, specificity of 96%, PPV of 77%, and NPV of 98%. Conclusion: In conclusion, calretinin IHC utilized in specimens seems superficial and inadequate; moreover, the association with the high specificity percentage (96%) could help physicians with less invasive biopsy methods, such as endoscopic rectal biopsy.